2008
DOI: 10.1088/0031-9155/53/9/010
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and bias in contrast concentration measurements using spoiled gradient echo pulse sequences

Abstract: Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) is a widely used technique for assessing tissue physiology. Spoiled gradient echo (SPGR) pulse sequences are one of the most common methods for acquisition of DCE-MRI data, providing high temporal and spatial resolution with strong T 1 -weighting. Conversion of SPGR signal to concentration is briefly reviewed, and a new closed-form expression for concentration measurement uncertainty for finite signal-to-noise ratio (SNR) and baseline scan time is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
267
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 197 publications
(277 citation statements)
references
References 35 publications
10
267
0
Order By: Relevance
“…[4] and [5], E 10 ¼ exp (ÀT R R 10 ) and E Ã 20 ¼ exp (ÀT E R Ã 20 ). E 2 * does not depend on R 20 *.…”
Section: ½3mentioning
confidence: 99%
See 4 more Smart Citations
“…[4] and [5], E 10 ¼ exp (ÀT R R 10 ) and E Ã 20 ¼ exp (ÀT E R Ã 20 ). E 2 * does not depend on R 20 *.…”
Section: ½3mentioning
confidence: 99%
“…Given the pulse sequence settings T R , T E , and a, the CA relaxivities r 1 and r 2 , and the tissue of interests relaxation time T 10 , Eq. [4] can be solved numerically to yield the most accurate solution for the CA concentration C num . Further details can be found in (4), where it is shown that Eq.…”
Section: ½3mentioning
confidence: 99%
See 3 more Smart Citations